Optimization of the crystallizability of a single-chain antibody fragment - Škerlová, Jana; Král, Vlastimil; Fábry, Milan; Sedláček, Juraj; Veverka, Václav; Rezáčová, Pavlína (Acta crystallographica. Section F, Structural biology communications, 2014)
Single-chain variable antibody fragments (scFvs) are molecules with immense therapeutic and diagnostic potential. Knowledge of their three-dimensional structure is important for understanding their antigen-binding mode as well as for protein-engineering approaches such as antibody humanization. A major obstacle to the crystallization of single-chain variable antibody fragments is their relatively poor homogeneity caused by spontaneous oligomerization. A new approach to optimization of the crystallizability of single-chain variable antibody fragments is demonstrated using a representative single-chain variable fragment derived from the anti-CD3 antibody MEM-57. A Thermofluor-based assay was utilized to screen for optimal conditions for antibody-fragment stability and homogeneity. Such an optimization of the protein storage buffer led to a significantly improved ability of the scFv MEM-57 to yield crystals.
Keywords: single-chain antibody fragment; sekvence aminokyselin; Thermofluor assay; oligomerization; jednořetězcové protilátky; Molecular Sequence Data; molekulární sekvence - údaje; Amino Acid Sequence; Single-Chain Antibodies; crystallizability optimization; lidé; Crystallization; crystallization; differential scanning fluorimetry; Chromatography, Gel; Humans; krystalizace; gelová chromatografie